ΔHR/ΔWR derived from CPET; A novel predictor of 'off' symptom in Parkinson's disease. (November 2021) - Yoshida, Kohsuke; Takano, Kazuki; Tani, Hiromi; Nobuhara, Sae; Maruyama, Yuki; Marumoto, Kohei
Abstract: Introduction: Chronotropic incompetence (CI) is broadly defined as the inability of the heart to increase its rate commensurate with increased activity. In this study, we tried to clarify the link between CI and UPDRS part II (off-on), which was calculated by subtracting part II (on) from part II (off), in patients with Parkinson's disease (PD). Methods: Thirty-six hospitalized patients were examined by using cardiopulmonary exercise testing (CPET) for exercise tolerance (ΔVO2/ΔWR and peak VO2/W) and the presence of CI (ΔHR/ΔWR), and using electrocardiogram for heart rate variability. Results: We originally divided the patients into three groups; Group I (ΔHR/ΔWR x100 <15) (N = 3), Group II (15≥, <60) (N = 28), Group III (>60) (N = 5). Since Group I and III were significantly smaller and older than Group II, we focused and divided into two groups; Group II CI (+), the PD patients with CI (15≤ ΔHR/ΔWR x100 <35), and Group II CI (−), those patients without that (35≤ ΔHR/ΔWR x100 <60). ΔVO2/ΔWR and peak VO2/W in CI (+) patients was lower than CI (−) ( P  = 0.022 and P  = 0.096, respectively). HF power (parasympathetic activity) tends to be decreased, whereas LF/HF ratio (sympathetic activity) was increased in CI (+) patients as compared with CI (−). The UPDRS part II (off-on) of CI (+) patients was significantly higher than CI (−) ( P  = 0.023). Conclusions: In PD patients, the difference between 'on' and 'off' in activities of daily living might be predicted by using ΔHR/ΔWR x100 obtained from CPET as an index. Highlights: The parameter of ΔHR/ΔWR can be obtained from CPET (Cardiopulmonary Exercise Testing). ΔHR/ΔWR was suitable for assessing the presence of CI (Chronotropic incompetence). The patients with Parkinson's disease (PD) who have CI, impaired an exercise tolerance. PD patients with CI had a difference in the UPDRS part II score when they were on and off. PD patients who have CI felt the difference between 'on' and 'off' in activities of daily living.